ZOOM-BASED LEARNING STAGES IN HIGHER EDUCATION - Fadhilah, Rizki Nur; Pratama, Andika Wahyu; Trapsilo, Yogi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
This research is crucial because, inevitably, learning in higher education has shifted to the digital realm, making Zoom a substitute classroom. Unfortunately, many instructors and students still feel that online lectures are less than optimal, often feeling like one-way lectures. To address this issue, our primary goal was to identify and develop the most appropriate and effective steps or stages for using Zoom in the classroom, from how instructors prepare, manage interactive sessions, and evaluate the results. We conducted this research using qualitative methods, distributing questionnaires to instructors and students who already have extensive experience with Zoom and observing how they actually teach and learn. We predict the emergence of a practical